Hubungan antara Tingkat Pengetahuan dan Sikap dengan Tindakan Pencegahan Penyakit Rabies pada Warga di Wilayah Puskesmas Kuta II - Ni Kadek Ayu Septiani Sarjana; Arsita Eka Prasetyawati; Dyah Ratna Budiani (Smart Medical Journal, 2018)
Introduction: Rabies is a disease of animals (usually vertebrate) which is zoonotic (transmissible to humans). Rabies occurs in 24 out of the 34 provinces of Indonesia. Rabies is caused by a virus in the Family: Rhabdivoridae, Genus: Lyssavirus. Control the dog population and dog vaccination is effective and economical method to prevent the incidences of rabies in humans. This study aims to investigate the relationship between level of knowledge and attitude to the practice in prevention rabies infection in residents lived in area covered by Puskesmas Kuta II.Methods: This study was a cross-sectional study and carried out by simple random sampling of 96 residents in the area of Puskesmas Kuta II. In this study, the independent variables are knowledge of and attitudes towards rabies disease while the dependent variable is the practice to prevent rabies infection in human. Data were collected by a questionnaire-based interview. Analyses were then carried out using the chi-square (x2) followed by multivariate analysis using multiple logistic regressions.Results: This study showed that knowledge has a significant relationship with practice for rabies disease prevention (p = 0.013; OR 4.240; 95% CI 1.352 up to 13.296). Attitude has a significant positive relationship with the value of practice for rabies disease prevention (p = 0.015; OR 3.073; 95% CI 1.233 up to 7.627). The combined effect of knowledge and attitudes to practice for rabies prevention were approximately 20.90% (Negerkerke R square = 0.209).Conclusions: There was a significant relationship between knowledge and attitudes with the practice for rabies disease prevention in residents in the area of Puskesmas Kuta II, the higher level of knowledge and improved attitudes will improve practice for rabies disease prevention amongst residents in the area of Puskesmas Kuta II. Key words: Rabies;  Rabies;  Preventio; Knowledge; Attitude;  Practice